2023
DOI: 10.3390/dj11080199
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of 3D-Printed Occlusal Splint Materials

Vladimir Prpic,
Filipa Spehar,
Dominik Stajdohar
et al.

Abstract: Data regarding the mechanical properties of three-dimensionally (3D) printed materials for occlusal splint manufacturing are scarce. The aim of the present study was to evaluate the flexural strength and surface hardness of modern 3D-printed occlusal splint materials and compare them with two control groups, namely, milled and conventional cold-polymerized occlusal splint materials. A total of 140 rectangular specimens were manufactured for the present study. The specimens were prepared in accordance with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Elution, deterioration, relaxation, accelerated crack growth, visco-elastic effects, and decreased wear resistance are all potential outcomes that might be brought about by these causes [31,[44][45][46]. Despite the fact that previous studies have demonstrated that the mechanical qualities of 3D printed materials are often inferior to those of milled materials, the technology of additive manufacturing represents a promising field for dentistry [47]. Within the scope of future studies, it is possible to incorporate a more extensive range of materials into a clinical environment (in vivo) in order to investigate the durability and clinical acceptance of these materials.…”
Section: Storagementioning
confidence: 99%
“…Elution, deterioration, relaxation, accelerated crack growth, visco-elastic effects, and decreased wear resistance are all potential outcomes that might be brought about by these causes [31,[44][45][46]. Despite the fact that previous studies have demonstrated that the mechanical qualities of 3D printed materials are often inferior to those of milled materials, the technology of additive manufacturing represents a promising field for dentistry [47]. Within the scope of future studies, it is possible to incorporate a more extensive range of materials into a clinical environment (in vivo) in order to investigate the durability and clinical acceptance of these materials.…”
Section: Storagementioning
confidence: 99%
“…While there is a growing body of work examining the mechanical properties of materials used in the additive manufacturing of occlusal splints [ 30 , 31 ], there remains a significant gap in the literature regarding how post-curing methods influence the mechanical properties of orthodontic aligner materials.…”
Section: Introductionmentioning
confidence: 99%